Rancang Bangun Kendali Tekanan Uap Air pada Tangki Pemanas Menggunakan Pengendali PID Berbasis PLC - Sofian Yahya; Sarjono Wahyu Jadmiko; Adnan Rafi Al Tahtawi; Reza Apriyanti (Fakultas Teknik Universitas Pancasila, 2021)
Process control is needed in various types of industries for production. The controlled process variables can be temperature, flow, pressure, and level. For this reason, an automatic control system with the right method is needed to produce quality products. This study aims to design and implement a steam pressure control system on a prototype heating tank using PID controller based on PLC. The pressure in the heating tank will be controlled to a set point of 10 kPa with a maximum steady-state error of 3%. PID control is designed using the Ziegler Nichols method which is then implemented on the PLC Omron CP1H with an MPX5500DP sensor to detect pressure. The results of the research obtained are that the PI controller can produce a better response when compared to the P and PID controllers. PI controller with parameters Kp = 1.23, Ti = 860, and Td = 0 can produce a response with a rise time of about 300 seconds and a steady-state error of 3.3%.